Antibiotic Use and Computed Tomography Imaging for Rhinosinusitis as Quality Metrics in Modern Health Care. Issue 6 (November 2019) - Xiao, Christopher C.; Kshirsagar, Rijul S.; Liang, Jonathan
Background: American Academy of Otolaryngology-Head and Neck Surgery rhinosinusitis guidelines have been adapted into quality measures intended to be a basis for adjusting physician reimbursement and as public information to help patients select physicians. Early and continual evaluation of these measures is therefore important, given the impacts these may have. Objective: To examine the metrics used in by Medicare for reimbursement in the Physician Quality Reporting System (PQRS) used in Merit-based Incentive Payment System (MIPS). Methods: This study is a retrospective review of the 2015–2016 Center for Medicare and Medicaid Services Physician Compare Initiative regarding quality metrics for acute and chronic rhinosinusitis for providers participating in MIPS. Results: Data for 726 providers were extracted from the PQRS database. Otolaryngologists had a low enrollment with less than 50 responding for any 1 measure. Of the reported quality metrics, otolaryngologists prescribed a significantly greater number of antibiotics than other providers within 7 days of diagnosis or within 10 days after symptom onset (48.3% vs 11.3%, P  < .001). There was a significant difference in the mean compliance between otolaryngologists and all other providers for the use of CT scans within 28 days of diagnosis (2.3% vs 0.2%, P  < .001). There was no significant difference in the mean compliance for the use of multiple CT scans within 90 days of diagnosis (2.0% vs 2.3%, P  = .8). Inverse metrics comprise 3 out of 4 measures. Conclusion: This review of the quality metrics used in MIPS shows several differences between otolaryngologists and nonspecialists, but raise concerns regarding applicability.